Fast start strategy induces different individual responses in velocity regulation during a 10 km race - Carmo, E. C.; Gil, S.; Kobal, R.; Roschel, H.; Urginowich, C.; Bertuzzi, R.; Tricoli, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The pacing regulation has an important impact on running performance. The fast start strategy (FS) has been frequently observed in 10km racing; but if this strategy is advantageous for performance is still controversial. Pacing regulation occurs with the purpose of protecting the body from harmful changes in homeostasis and a FS may induce premature fatigue subsequently hampering runner`s performance. It seems that the RPE may be an efficient way to monitor pacing regulation (Abiss and Laursen, 2008). Thus, the aim of this study was to verify the regulation of pacing strategy and the associated RPE when a FS was applied. Methods: Fifteen runners participated in two simulated 10km races. Running velocity (GPS Polar, RS800CX, Finland) and RPE (Borg 6-20) were measured every 400m. The pacing strategy was evaluated by the velocity-distance curve. The first race was a free pacing (FP) running (runners were instructed to complete the race as fast as possible) and in the 2nd race a FS was applied (runners performed the 1st km 6% faster than the FP). Results: There was no difference in 10 km performance between strategies (45.0 ± 4.1 vs 45.2 ± 4.8 min). In the FP running the first 400m were faster than rest of the race (p<0.001). In the FS velocity was higher in initial 1000m (p<0.001). Afterwards there was no difference in velocity between groups. The FS presented a higher RPE in the first 1600m when compared to FP (10.5 ± 1.8 vs 12.3 ± 1.8, p<0.04). Seven runners improved performance in 2.4% using FS (43.9 ± 2.9 vs 42.9 ± 2.4, p< 0.01) while the other eight showed a 3.2% decrement (46.2± 5.2 vs 47.8 ± 5.6, p< 0.001). Discussion: We found that the regulation of the pacing strategy was not affected by the use of FS. There was no difference in performance between FP and FS. However, dividing the subjects into positive (PR) and negative responsive (NR) we observed that the PR group ran faster than the NR group during the FS race. Interestingly, the 10km RPE was similar between groups. During running the momentary RPE is compared to the runners` expected RPE which is affected by their previous experience and the remaining running distance (Tucker, 2009). Thus, it seems that individual differences in pacing regulation cannot be monitored by the RPE.